2021
DOI: 10.1093/jb/mvab021
|View full text |Cite
|
Sign up to set email alerts
|

Nanog-mediated stem cell properties are critical for MBNL3-associated paclitaxel resistance of ovarian cancer

Abstract: Paclitaxel (PTX) is the standard first-line treatment of ovarian cancer, but its efficacy is limited by multi-drug resistance. Therefore, it is crucial to identify effective drug targets to facilitate PTX-sensitivity for ovarian cancer treatment. Seventy PTX-administrated ovarian cancer patients were recruited in this study for gene expression and survival rate analyses. Muscleblind-like-3 (MBNL3) gain- and loss-of-function experiments were carried out in ovarian cancer cells (parental and PTX-resistant) and x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… 31 Previous studies demonstrated that MBNL3 affects radio sensitivity and paclitaxel resistance in carcinogenesis. 32 , 33 MBNL3 is overexpressed in HCC, although likewise PSAT1. However, MBNL3 is an HCC-specific oncofetal protein for the unique therapeutic target of HCC, which overexpressed in fetal liver tissues, silenced in adult liver and reproduced in HCC tissues.…”
Section: Discussionmentioning
confidence: 98%
“… 31 Previous studies demonstrated that MBNL3 affects radio sensitivity and paclitaxel resistance in carcinogenesis. 32 , 33 MBNL3 is overexpressed in HCC, although likewise PSAT1. However, MBNL3 is an HCC-specific oncofetal protein for the unique therapeutic target of HCC, which overexpressed in fetal liver tissues, silenced in adult liver and reproduced in HCC tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have proved that MBNL3 is involved in regulating the progression of some cancers through serving as a facilitator [ 6 - 9 ]. Nevertheless, the regulatory functions of MBNL3 in GAC remain vague.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports revealed that MBNL3 expression is dysregulated in diversified cancers, thereby affecting tumor growth and development. For instance, higher expression of MBNL3 is positively associated with PTX resistance and results in poor prognosis in ovarian cancer [ 6 ]. In addition, MBNL3 affects cell invasion in pancreatic ductal adenocarcinoma [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of CASP3 transcription has been found to suppress the proliferation of cancer cells and to promote cell apoptosis in multiple cancers ( Li et al, 2016 ; Luo et al, 2018 ; Zhu et al, 2019 ). MBNL3 participates in paclitaxel resistance in ovarian cancer ( Sun et al, 2021 ). SEPT2 is required for the progression of human breast cancer via MEK/ERK activation ( Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%